DAMPAK PEMBANGUNAN ABDUL RASYID TOWER TERHADAP PERUBAHAN ARUS LALU LINTAS DI KABUPATEN KOTAWARINGIN BARAT (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2024)
In line with population growth, Pangkalan Bun City has now expanded to include linear pathways or the surrounding area, not only in the city center. This has resulted in the City of Pangkalan Bun having many large trading centers and one of them is the construction of the Abdul Rasyid Tower on Jalan Udan Said in front of the CBI Group head office, Pangkalan Bun, West Kotawaringin Regency, which will result in congestion / attraction of new trips in Pangkalan Bun City. Data collection was carried out by means of a direct survey at the Abdul Rasyid Tower intersection on Jalan Udan Said during peak hours in the morning, afternoon and evening from 06.00 – 18.00 WIB. From the survey results, grouping was carried out on each segment at the intersection and presented in the form of a vehicle table. In calculating the savings analysis using the 1997 Indonesian Highway Capacity Manual and Vissim Software. Traffic performance around the Abdul Rasyid Tower project site at the time prior to construction according to MKJI 1997 calculations, the biggest delay at the afternoon intersection at the first intersection was 7,45 second. The results of the Vissim Software the biggest intersection delay occurred in the morning at the first intersection, which was 7,98 second. Traffic performance around the Abdul Rasyid Tower project site during construction according to MKJI 1997 calculations, the largest intersection delay occurred in the afternoon at the first intersection of 9,47 second. The results of the Vissim Software, the biggest delay at the intersection occurred in the afternoon at the first intersection at 9,89 second. Traffic performance around the Abdul Rasyid Tower project site during post-construction according to MKJI 1997 calculations, the largest intersection delay during the day at the first intersection was 7,78 second. The results of the Vissim Software, the largest delay at the first intersection during the day is 8,21 second.